The Methodology of the Operating Cost Accounting in Identifying Mileage of Efficient Motor Vehicle Operation - Terentiev, Aleksey Vyacheslavovich; Menukhova, Tatiana Anatol’yevna (International Journal of Economics and Financial Issues, 2015)
The article considers the current approach to the calculation of unit costs for maintenance and repair of the rolling stock of the automobile transport. In order to more accurately determine unit costs and the moment of the write-off of a car, the method of cost accounting for the operation of motor vehicles has been developed. The proposed method is of operational nature. Unlike the existing approach, it allows to track the intensity of cost increment at a constant total aggregate cost. Since the maintenance operation interval is a constant measure of the technical condition of any vehicle, this method allows comparing the intensity of cost changes for various models of cars within their class. Thus, it can be one of the criteria for the scientific substantiation of the selection of transportation vehicles. Keywords: unit cost, maintenance operation, auto service, write-off time, operation. JEL Classifications: D46; O31